Acute pancreatitis as first presentation of primary hyperparathyroidism: an observational study at tertiary care centre Jammu and Kashmir, India - Chesti, Mohmad Saleem; Gazala, Sheenam; Imran, Ali (International Journal of Advances in Medicine, 2022)
Metabolic causes of acute pancreatitis though uncommon, are important as early recognition helps in the management and prevention of recurrent episodes. Among the uncommon etiologies, Primary hyperparathyroidism (PHPT) is one of the important causes of acute pancreatitis. We studied nine patients with acute or recurrent acute pancreatitis with etiology of PHPT. All patients had elevated serum calcium on admission and high levels of circulating parathyroid hormone. Ultrasonography, 4D CT and Sestamibi scan was used to localize parathyroid adenoma. These patients underwent parathyroidectomy and post-operative histology was consistent with parathyroid adenoma.